A comparative study of protein and enzymatic activity in venoms of some common wasps (Hymenoptera: Vespidae) from São Paulo State - Da Silva, Giselly Pereira [UNESP]; Brochetto-Braga, Márcia R. [UNESP]; Ruberti, Maristela [UNESP]; Ternero, Marcos Lima [UNESP]; Gobbi, Nivar [UNESP] (My University, 2004)
The Hymenoptera Aculeata venoms, with few exceptions, have been poorly studied and characterized. Nevertheless, they have raised increasing interest due to their medical importance, since accidents with these insects are fairly frequent in Brazil and may cause severe allergic reactions. The objectives of the present work were the quantitative characterization of the main allergenic enzymes present in the venom of the species Polybia paulista, Polybia ignobilis, Polistes simillimus, and Agelaia pallipes pallipes through biochemical assays for the determination of total protein content, as well as the level of the enzymatic activity of phospholipase, hyaluronidase, acid phosphatase and esterase. These results, in addition to providing biochemical knowledge about the venom of the species in question, also supply studies that allow phylogenetic inferences among them.
Keywords: Agelaia pallipes pallipes; Enzymes; Polistes simillimus; Polybia ignobilis; Polybia paulista; Protein; Venom; Vespidae; Aculeata; Agelaia; Hexapoda; Hymenoptera; Insecta; Polistes; Polybia